2013
DOI: 10.3748/wjg.v19.i47.9111
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mosapride plus proton pump inhibitors for treatment of gastroesophageal reflux disease: A systematic review

Abstract: Mosapride combined therapy is not more effective than PPI alone as first-line therapy. Whether it is effective in PPI-resistant patients needs to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
20
1
2
Order By: Relevance
“…Overall, their effect is modest. A systematic review that compared the efficacy of mosapride plus PPI with PPI monotherapy in GORD did not show any benefit 98. The addition of mosapride to PPI was shown to improve symptoms in patients with GORD with dysmotility symptoms 99–101.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, their effect is modest. A systematic review that compared the efficacy of mosapride plus PPI with PPI monotherapy in GORD did not show any benefit 98. The addition of mosapride to PPI was shown to improve symptoms in patients with GORD with dysmotility symptoms 99–101.…”
Section: Resultsmentioning
confidence: 97%
“…Mosapride is a 5-HT 4 receptor agonist and can stimulate upper gastrointestinal movement [ 34 ], accelerate gastric emptying [ 35 ] and colonic motility [ 36 , 37 ], and improve stool frequency and consistency, especially in patients with irritable bowel syndrome with constipation (IBS-C) [ 38 ] and/or functional constipation [ 37 ]. Consequently, the effects of EA during the treatment and follow-up periods can be more accurately revealed by using mosapride as the controlled intervention.…”
Section: Discussionmentioning
confidence: 99%
“…3537 These studies were included in a 2013 systematic review reporting that mosapride combination therapy with PPI is no more effective than PPI alone. 38 However, in a subgroup analysis, patients with more severe symptoms experienced a slight benefit compared to placebo. 36 Two subsequent studies similarly found no improvement in GERD symptoms with combination mosapride therapy, also noting lower response rates in NERD as compared to EE.…”
Section: Adjunctive Medical Therapiesmentioning
confidence: 99%